Transient Increase in Cortical Excitability Following Static Stretching of Plantar Flexor Muscles - Budini, Francesco; Christova, Monica; Gallasch, Eugen; Kressnik, Paul; Rafolt, Dietmar; Tilp, Markus (Frontiers in Physiology, 2018)
Spinal excitability in humans is inhibited by both passively holding a static position with the muscle lengthened (static stretching) and by a single non-active lengthening movement. However, whilst immediately after a passive lengthening movement the inhibition persists for several seconds, there seem to be an immediate recovery following static stretching. This result is counter intuitive and could be attributed to methodological procedures. Indeed, differently to what has been done until now, in order to study whether static stretching has a transient effect on the neuromuscular pathway, the procedure should be repeated many times and measurements collected at different time points after stretching. In the present study we repeated 60 times 30 s static stretching of ankle plantar flexors and measured tap reflex (T-reflex), Hoffman reflex (H-reflex) and motor evoked potentials (MEPs) from the Soleus muscle at several time points, starting from immediately after until 30 s following the procedure. T-reflex was strongly inhibited (range 31-91%, p=.005) and the inhibition persisted for 30 s showing a slow recovery (r=.541, p=.037). H-reflex was not affected by the procedure. Stretching increased the size of the MEPs (p < .0001), differences at times 0 s and 2 s after stretching (p = .015 and p = .047 respectively). These results confirm that static stretching reduces muscle spindle sensitivity and suggest that pre and postsynaptic mechanisms are conditioned in opposite ways by this procedure.